Edukasi Zoonosis dan Pemberian Booklet Vaksinasi sebagai Upaya Pencegahan Zoonosis pada Peternak Sapi di Kecamatan Manonjaya Kabupaten Tasikmalaya - Aprila Arianti; Septiani Tri Windianti; Nazwa Salsabila; Ninda Salma Nurfitri; Deborah Maria Magdalena Nababan; Muhammad Ziyan Arfad (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The high risk of zoonotic disease transmission in cattle farming environments necessitates effective education to enhance workers' understanding and hygienic behaviors. This study aims to improve workers' awareness and hygienic practices in preventing zoonotic diseases through an outreach program at Manonjaya Farm. The method used is a case study with a qualitative approach, involving semi-structured interviews and direct observation. The educational activities were conducted interactively using posters, lectures, and demonstrations of the six-step Handwashing with Soap (CTPS) technique. The results indicate an increase in workers' understanding of zoonotic risks, particularly bovine tuberculosis, as well as the importance of maintaining barn cleanliness, regular vaccinations, and the use of personal protective equipment. Furthermore, the CTPS practice successfully enhanced workers’ skills and consistency in implementing hygienic behaviors. Supporting strategies such as the installation of educational posters, distribution of vaccination logbooks, and provision of handwashing soap contributed to the sustainability of behavioral changes. These findings affirm the effectiveness of interactive lectures and demonstrations in improving knowledge and preventive measures against zoonotic diseases within farming communities, aligning with the One Health approach.